Increasing the Carrier Injection Efficiency of GaN-Based Ultraviolet Light-Emitting Diodes by Double Al Composition Gradient Last Quantum Barrier and p-Type Hole Supply Layer - Jinxing Wu; Peixian Li; Xiaowei Zhou; Jiangtao Wu; Yue Hao (IEEE Photonics Journal, 2021)
A 365 nm AlxGa1-xN-based ultraviolet light-emitting diodes (LEDs) with double Al composition gradient last quantum barrier and hole supply layer structure has been studied. Experimental results show that the proposed structure enhances the carrier injection efficiency and suppresses the overflow of electrons. The introduction of three-dimensional hole gas further enhances the hole injection efficiency. As a result, the wall plug efficiency and electroluminescence intensity are significantly improved. In addition, the carrier concentration and the radiative recombination rate in the active region of the quantum well increases. Looking at the energy band diagram, one sees that the double Al composition gradient structure leads to higher electron blocking and alleviates the hole blocking effect. Overall, we conclude that the double Al composition gradient structure provides a pathway to achieve high-efficiency ultraviolet LEDs.